2013
DOI: 10.1590/0037-8682-0093-2013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical features of celiac disease in patients with hepatitis B virus infection in Southern Brazil

Abstract: Introduction: Celiac disease is an autoimmune disorder that involves gluten intolerance and can be triggered by environmental factors including hepatitis B virus (HBV) infection. This study aimed to describe the prevalence of celiac disease in individuals with HBV infection and to describe the clinical and laboratory characteristics of celiac disease associated with HBV. Methods: This cross-sectional study included 50 hepatitis B patients tested for IgA anti-endomysial antibodies (EMAs) and tissue antitransglu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
1
6
0
2
Order By: Relevance
“…In the results of the statistical analysis of the current study, the levels of urea, creatinine, and uric acid appeared close to normal levels, and some suffered from a slight increase in the levels of urea, creatinine and uric acid, and others in which the level of creatinine and uric acid decreased below the normal level in patients who take gluten, and this indicates the occurrence of disturbance in the function of the kidneys, which is an indication of the onset of celiac disease effect on kidney function .The results of the current study are in agreement with the study that showed a slight increase in the level of uric acid and a non-significant decrease in the level of creatinine in patients eating gluten compared to healthy subjects [9] .The results of the current study also agreed with the study in which glucose levels came within the normal range, but the levels of creatinine, urea and uric acid showed an increase from the normal range of the studied cases, as the researcher proved that there is a clear relationship between celiac disease and kidney disease [ 10 ] A study of celiac patients who also suffered from hepatitis B virus indicated that the creatinine level in some of the studied cases decreased below normal levels [11]. Another study showed that there is a high level of creatinine in patients with celiac disease and www.minarjournal.com kidney disease who eating gluten [6].…”
Section: Discussionsupporting
confidence: 89%
“…In the results of the statistical analysis of the current study, the levels of urea, creatinine, and uric acid appeared close to normal levels, and some suffered from a slight increase in the levels of urea, creatinine and uric acid, and others in which the level of creatinine and uric acid decreased below the normal level in patients who take gluten, and this indicates the occurrence of disturbance in the function of the kidneys, which is an indication of the onset of celiac disease effect on kidney function .The results of the current study are in agreement with the study that showed a slight increase in the level of uric acid and a non-significant decrease in the level of creatinine in patients eating gluten compared to healthy subjects [9] .The results of the current study also agreed with the study in which glucose levels came within the normal range, but the levels of creatinine, urea and uric acid showed an increase from the normal range of the studied cases, as the researcher proved that there is a clear relationship between celiac disease and kidney disease [ 10 ] A study of celiac patients who also suffered from hepatitis B virus indicated that the creatinine level in some of the studied cases decreased below normal levels [11]. Another study showed that there is a high level of creatinine in patients with celiac disease and www.minarjournal.com kidney disease who eating gluten [6].…”
Section: Discussionsupporting
confidence: 89%
“…However, it is still a controversy as to whether viral hepatitis (HBV and HBC) is associated with CD (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…The association between CD and various liver diseases has been confirmed, including cryptogenic hypertransaminasemia, autoimmune liver disease (autoimmune hepatitis, primary sclerosing cholangitis, primary biliary cirrhosis), NAFLD, and nonalcoholic steatohepatitis (3). However, it is still a controversy as to whether viral hepatitis (HBV and HBC) is associated with CD (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have addressed the relationship between celiac disease and chronic hepatitis B [29,30], and the results are controversial. It has been demonstrated that vaccines against the hepatitis B virus are less efficacious in patients with celiac disease [31,32].…”
Section: Celiac Disease and The Livermentioning
confidence: 99%